2019
DOI: 10.3390/su11030576
|View full text |Cite
|
Sign up to set email alerts
|

National Green GDP Assessment and Prediction for China Based on a CA-Markov Land Use Simulation Model

Abstract: Green Gross Domestic Product (GDP) is an important indicator to reflect the trade-off between the ecosystem and economic system. Substantial research has mapped historical green GDP spatially. But few studies have concerned future variations of green GDP. In this study, we have calculated and mapped the spatial distribution of the green GDP by summing the ecosystem service value (ESV) and GDP for China from 1990 to 2015. The pattern of land use change simulated by a CA-Markov model was used in the process of E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…Compared with existing research, some of our results are controversial or contrary, such as the function of relationships between ESV and the GDP, light index, and population values. Yu found that the ESVs of China was decreased slightly while the GDP value was increased substantially [43]. However, Xie found that there is no linear relationship between the total ESV and GDP [5].…”
Section: Plos Onementioning
confidence: 98%
“…Compared with existing research, some of our results are controversial or contrary, such as the function of relationships between ESV and the GDP, light index, and population values. Yu found that the ESVs of China was decreased slightly while the GDP value was increased substantially [43]. However, Xie found that there is no linear relationship between the total ESV and GDP [5].…”
Section: Plos Onementioning
confidence: 98%
“…They lead to low carbon emissions, use of natural resources efficiently, and be socially inclusive. The economic sectors of production that directly impact the environment should be encouraged through viable and reasonable alternatives by the public sector in general [52,53], as expressed in Figure 2.…”
Section: Manufacturing Industrymentioning
confidence: 99%
“…There are insufficient approaches for land use land cover change prediction which include Cellular and Hybrid models, Markov Chain and Cellular Automata Analysis (Ca-Markov) Mode (Katana et al, 2013). The CA-Markov Model is suitable for land use land cover simulations (Hyandye and Martz, 2017;Yu et al, 2019;Yulianto et al, 2019). This is because they consider the spatiotemporal dynamics of land use land cover changes (Ghurah et al, 2018).…”
Section: Introductionmentioning
confidence: 99%